Pembuatan Produk Olahan Berbahan Kulit Buah Manggis kepada Kelompok Tani Permata Harapan Kampung Manggis Kecamatan Pauh Kota Padang - Fitri Wahyuni; Yahdian Rasyadi; Wida Ningsih; Amri Bakhtiar; Eka Desnita (LPPM UNIVERSITAS DIAN NUSWANTORO, 2024)
Kampung Manggis is a mangosteen producing area in Pauh, Padang city. When a large number of mangosteens are produced, but not all of them are sold by the mangosteen farmers, the remaining mangosteens will rot over time. The remaining mangosteen, which cannot be sold can be developed into various useful health products. The mangosteen peel contains various beneficial chemical ingredients, one of which is alpha mangostin. Based on various research results, it is stated that alpha mangostin has antioxidant activity. The community service which was held on June 23 2023 in Kampung Manggis as a service partner was the Permata Harapan farmer group. This community service is carried out by teaching how to make products from mangosteen peel processed into facial mask and body scrub products. From the processing of mangosteen peel, two products are produced which are made together with the community, namely a mangosteen skin facial mask and body scrub. Mangosteen farmers from the Permata Harapan farmer group can optimize the productivity of all the mangosteens harvested and no more mangosteens will become waste.